Pembentukan Karakter Anak Usia Sekolah Dasar Melalui Permainan Tradisional - Harun Joko Prayitno; Faradiyah Nurul Rahmawati; Khoirunnisa’ Ismi Nur Intani; Fajar Gemilang Pradana (Yayasan Keluarga Guru Mandiri, 2022)
Character education is a series of efforts to educate children to behave well, make the right decisions, and participate in positive societal contributions. The problem is that traditional games have started to disappear because, currently, elementary school-aged children prefer modern games. The advantages of traditional games are messages related to togetherness, culture, and morals. Community service aims to foster character in elementary school-aged children. The method of implementing the activities is socialization and direction related to traditional games shaping the character of elementary school-aged children. Activities are carried out by providing direct guidance to children when playing games. The result of this service program is that the program to socialize the importance of traditional games and the cheerful playing movement to foster the character of elementary school-aged children is carried out well. The activities conclude that the character formation of elementary school-aged children can be done through traditional games.